Prognostic Factors Associated with the Efficacy of Hepatic Transarterial Embolization in Patients with Neuroendocrine Tumors - Jose Eduardo Nuñez; Charles Zurstrassen; Milton Barros; Deise Uema; Rossana Lopez; Rachel Riechelmann (Brazilian Journal of Oncology)
Introduction: To evaluate the safety and efficacy of hepatic transarterial embolization (TAE) or transarterial chemoembolization (TACE) in patients with irresectable liver metastases from neuroendocrine tumors (NETs) treated at two Brazilian cancer centers. Methods: Retrospective multicenter analysis of patients (pts) with histological diagnosis of neuroendocrine tumor of any origin with unresectable and measurable hepatic metastases who underwent at least one procedure of TAE or TACE. Endpoints: Hepatic progression free survival (HPFS), overall survival (OS), tumor response and toxicity assessment. Results: Thirty-six pts were evaluated. Primary tumors were as follow: midgut 20 pts, pancreas 7 pts, others 9 pts. Most of patients had grade (G) 1-2 tumors (93.3%). In patients with functioning NETs, clinically significant symptomatic control was 41.7%. Concerning type of embolization (TAE vs TACE), there were no significant differences in the proportion of patients achieving reduction of at least 50% of 5HIAA (45.5% vs 50%) and radiological disease control rate (91.3% vs 92.3%), respectively. In a median follow up of 40.8 months (m), median HPFS was 38.9m, and mean OS was 98m (median not reached). No significant differences were found in HPFS or OS by type of embolization procedure. Pancreatic primary tumor and G3 tumor by WHO classification were associated with significantly shorter HPFS. Tumor G3 was also associated with shorter OS. Adverse events of any grade were: abdominal pain (13.8%), fever (5.5%), and 2 pts developed biloma. Conclusion: Our study is the first in our region reporting results of TAE/TACE in patients with irresectable liver metastases from NETs. We observed that pts with pancreatic or G3 NET derive less benefit from these procedures. In pts with G1-2 NETs, both techniques offer similar results.